Participatory Management: Synergy Between School Committees and Parents in Accelerating the Short Surah Memorization Program - Rohmiasih Rohmiasih; Saryanto Saryanto; Jumintono Jumintono (CV. Edujavare Publishing, 2026)
This study examines the implementation of participatory management through the synergy between school committees and parents in accelerating the short surah memorization program at Banjar Public Elementary School, Kertek District, Wonosobo Regency, during the 2026/2027 academic year. The study employed a qualitative case study approach involving the principal, teachers, school committee members, parents, and students as research participants. Data were collected through interviews, observations, and document analysis, and were analyzed using data reduction, data display, and conclusion-drawing techniques. The findings reveal that participatory management was effectively implemented through collaborative planning, shared decision-making, open communication, stakeholder involvement, and continuous monitoring and evaluation. The synergy between school committees and parents significantly contributed to the success of the memorization program by providing motivational support, facilitating learning resources, strengthening supervision, and creating a conducive learning environment both at school and at home. This collaboration enhanced students’ memorization achievement, learning discipline, religious awareness, and commitment to Qur’anic learning. The study concludes that participatory management supported by strong partnerships between school committees and parents is an effective strategy for improving the implementation of religious education programs and promoting holistic student development. The findings provide valuable insights for schools seeking to strengthen stakeholder participation in achieving educational goals.